Primary thrombophilia in Mexico: a single tertiary referral hospital experience. Issue 8 (December 2016) - Lacayo-Leñero, Dennis; Hernández-Hernández, Darinel; Valencia-Martínez, Andrés; Barrales-Benítez, Olga; Vargas-Ruiz, Angel G.
Abstract : Thrombophilia is a complex hypercoagulable state that increases the risk of thrombosis. Most reports in medical literature of the Mexican population with this disease lack statistical validity. Therefore, the aim of this study is to describe the prevalence of primary thrombophilia in a tertiary referral hospital in Mexico. This is a study of patients referred to our hospital because of a hypercoagulable state and who later on were diagnosed with primary thrombophilia. The thrombophilia workup included methylenetetrahydrofolate reductase (MTHFR) C677T, antiphospholipid antibodies, protein C, protein S, antithrombin, factor VIII, factor V Leiden, prothrombin mutation G20210A, activated protein C resistance, JAK2 V617F and homocysteine. Ninety-five individuals were tested. The MTHFR C677T polymorphism was the most frequent anomaly in 84.1% of the tested individuals. There was a relatively low prevalence of factor V Leiden (5.2%) and anticoagulant protein deficiency (8.3%). The MTHFR C677T polymorphism has a very high prevalence compared with the low prevalence of anticoagulant protein deficiency and factor V Leiden mutation in Mexicans.